Synthesis of lipophilic 1-deoxygalactonojirimycin derivatives as D-galactosidase inhibitors - Schitter, Georg; Scheucher, Elisabeth; Steiner, Andreas J.; Stütz, Arnold E.; Thonhofer, Martin; Tarling, Chris A.; Withers, Stephen G.; Wicki, Jacqueline; Fantur, Katrin; Paschke, Eduard; Mahuran, Don J.; Rigat, Brigitte A.; et al. (Beilstein Journal of Organic Chemistry, 2010)
N-Alkylation at the ring nitrogen of the D-galactosidase inhibitor 1-deoxygalactonojirimycin with a functionalised C6 alkyl chain followed by modification with different aromatic substituents provided lipophilic 1-deoxygalactonojirimycin derivatives which exhibit inhibitory properties against β-glycosidases from E. coli and Agrobacterium sp. as well as green coffee bean α-galactosidase. In preliminary studies, these compounds also showed potential as chemical chaperones for GM1-gangliosidosis related β-galactosidase mutants.
Keywords: chemical chaperones; 1-deoxy-D-galactonojirimycin; iminosugars; lipophilic galactosidase inhibitor; N-modified iminosugars